2016
DOI: 10.1136/bjsports-2016-096795
|View full text |Cite
|
Sign up to set email alerts
|

Associations of occupational standing with musculoskeletal symptoms: a systematic review with meta-analysis

Abstract: Objective: Given the high exposure to occupational standing in specific occupations, and recent initiatives to encourage intermittent standing among white-collar workers, a better understanding of the potential health consequences of occupational standing is required.We aimed to review and quantify the epidemiological evidence on associations of occupational standing with musculoskeletal symptoms.Design: A systematic review was performed. Data from included articles were extracted and described, and meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 75 publications
(183 reference statements)
5
55
1
1
Order By: Relevance
“…This suggests that spending more time standing at school may not cause additional lower limb discomfort, even though these joints take more load in standing and prolonged occupational standing is associated with lower limb and back discomfort [33]. Weight shifting or the use of the fidget bar could have contributed to this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that spending more time standing at school may not cause additional lower limb discomfort, even though these joints take more load in standing and prolonged occupational standing is associated with lower limb and back discomfort [33]. Weight shifting or the use of the fidget bar could have contributed to this.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies have explored the effects of standing desks on musculoskeletal discomfort in children and results from these studies were inconsistent [31,32]. Given that research that has examined the association of occupational standing with musculoskeletal symptoms in adults has found that prolonged standing in adults is associated with the development of low back pain [33], it is important to examine the relationship between standing and musculoskeletal symptoms in children. If standing desks prove to be effective in increasing standing time and decreasing sitting time in children, while not causing excessive musculoskeletal discomfort, schools would have more reasons to implement these desks in classrooms.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have emphasized health risks associated with excessive sitting during the workday ( 8 ); however, excessive standing on the job also has been linked to adverse health outcomes ( 9 ). A systematic review of peer-reviewed articles on musculoskeletal symptoms and occupational standing as the main exposure variable found that occupational standing is associated with low back pain; however, associations with lower and upper extremity symptoms were inconclusive ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of peer-reviewed articles on musculoskeletal symptoms and occupational standing as the main exposure variable found that occupational standing is associated with low back pain; however, associations with lower and upper extremity symptoms were inconclusive ( 9 ). More research is needed to understand how to balance time spent sitting and standing while at work.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the risk of back pain with prolonged standing, as shown in recent reviews of laboratory10 and field11 evidence.…”
mentioning
confidence: 99%